2015
DOI: 10.1007/s40089-015-0139-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Mn-doped ZnS nanoparticles

Abstract: Mn-doped ZnS nanoparticles are synthesized by simple and cost effective chemical precipitation method. This diluted magnetic semiconductor is characterized by various techniques such as energy dispersive X-ray analysis, scanning electron microscopy, X-ray diffraction, photoluminescence and UV-Vis spectroscopy. High purity of the sample is confirmed by energy dispersive X-ray analysis. Sub-micrometer nanocrystals are observed using scanning electron microscope. Hexagonal phase of the material is confirmed by X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Thus, the synthesis of ZnO nanoparticles by direct precipitation method is simple, fast and eco-friendly in nature [7]. Recently, Mn-doped ZnO nanoparticles was used in the optical device in diluted magnetic semiconductor materials [8].The Cu-doped ZnO has sensor RT sensitivity, faster response time, and good selectivity. Miniaturized Cu-doped ZnO rod based sensor can server as a good candidate for effective H2 detector with low power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the synthesis of ZnO nanoparticles by direct precipitation method is simple, fast and eco-friendly in nature [7]. Recently, Mn-doped ZnO nanoparticles was used in the optical device in diluted magnetic semiconductor materials [8].The Cu-doped ZnO has sensor RT sensitivity, faster response time, and good selectivity. Miniaturized Cu-doped ZnO rod based sensor can server as a good candidate for effective H2 detector with low power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Within the different TMs, Mn was chosen as the rst doping material since it improves the emission properties, enhances the electrical, microstructural and optical characters and also possesses better photo and thermal stability [8]. Chandrasekar et al [9] discussed the variation in Urbach energy, Stokes's shift and steepness values in Mn added ZnS synthesized by co-precipitation technique. Ashkarran et al [10] revealed the decrease of photo-catalytic removal e ciency with the help of Bromocresol Green, Rhodamine B, and Bromochlorophenol Blue dyes in Mn added ZnS than un-doped ZnS.…”
Section: Introductionmentioning
confidence: 99%
“…The optical and structural evaluation of Mn or Cu doped ZnS [9][10][11] is available in the literature but the complete studies on Mn and Cu dual doped ZnS is nearly scanty. Therefore, Mn and Cu dual doped ZnS have been synthesized using co-precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore Mn 2+ helps in the production of improved luminescence properties along with the variation in particle size . The beneficial properties of Mn‐doped ZnS nanocrystals have created resounding interest among researchers who wish to develop these type of materials in different synthetic ways and explore their optical properties …”
Section: Introductionmentioning
confidence: 99%
“…[1] The beneficial properties of Mn-doped ZnS nanocrystals have created resounding interest among researchers who wish to develop these type of materials in different synthetic ways and explore their optical properties. [8][9][10] In our previous study, we reported the chemical precipitation and hydrothermal synthesis process for achieving semiconductor nanocrystals using different capping agents i.e. ZnS as host material and Mn 2+ as dopant.…”
Section: Introductionmentioning
confidence: 99%